Developing Business Continuity by Relying on Green Process Innovation Performance - Setyawan, Nanang Adie; Riyadi, Riyadi -; Suwardi, Suwardi -; Saptianing, Saptianing -; Setiawan, Andi - (Admisi dan Bisnis, 2023)
Business continuity is an interesting phenomenon to research. Because business has very intense competition. The purpose of this study is to build Green Process Innovation Performance from Green Strategic Intent with the help of intervening Green Intellectual Capital described by Green Human Capital, Green Organizational Capital, Green Relational Capital. The population of this study were the actors of Batik Tulis Lasem SMEs in Rembang Regency. While the sampling technique used in this study is the Census Method. The number of research samples was 115 samples from the total population of respondents. This research technique uses Path Analysis with SPSS version 25. The output of the model in this study can make a positive contribution to the actors of SMEs Batik Tulis Lasem in an effort to be able to realize the continuity and sustainability of their business in environmental aspects, both in the form of managerial implications and formulation of scientific articles and measurement instruments. Managerial advice is aimed at the local government in formulating program policies to maintain the existence of entrepreneurs after the Covid 19 Pandemic